Indigenous arbuscular mycorrhizal fungi at tangerine cv. Tejakula (Citrus reticulata cv. Tejakula) plantations, their colonization of the roots, and their effect on soil fertility - Wijana, Gede; Rai, I Nyoman; Mayadewi, Ni Nyoman Ari; Astiari, Ni Komang Alit (Brawijaya University, 2025)
Tangerines (Citrus reticulata var. Tejakula) were destroyed in 1984 by CVPD, allegedly because the use of chemicals was too intensive, resulting in land degradation. Since ten years ago, these oranges have been successfully cultivated again using healthy organic cultivation, but farmers have difficulty getting organic fertilizer. This research aimed to identify and isolate the Arbuscular Mycorrhizal Fungi (AMF) on tangerines cv. Tejakula, their colonization of the roots and effect on soil fertility. Exploration was conducted by collecting root and soil samples in tangerine cv. Tejakula production centers are in the Tejakula District, Buleleng Regency. Spore isolation was conducted using wet filtration and centrifugation techniques, while root colonization by AMF was carried out using the staining method with trypan blue. The isolated spores are composited into AMF biofertilizer using volcanic sand as a carrier medium. The biofertilizer was then tested for its effect on soil fertility with three treatment levels of AMF spore doses (0, 20, and 40 spores/50 g of carrier media per plant). The results of exploration, isolation, and identification showed that three genera and six species of AMF were found. The spore density ranged from 17 to 32 per 100 g of soil (mean 24.17 ± 2.02 spores). The average root colonization by AMF was very high, ranging from 90 to 100%, and the application of AMF biofertilizer at a dose of 20 and 40 spores per plant provided soil fertility was much better than the control (0 AMF spores per plant).